The Dilemma of Multicultural Education in Improving Quality: A Systematic Review - Suncaka, Eko (CV. Tripe Konsultan, 2024)
Multicultural education is an approach that integrates cultural diversity into the education system to create an inclusive and equitable learning environment. Multicultural education in improving quality is an effort to ensure that all students, regardless of cultural background, receive a high-quality education. This research aims to review several articles on multicultural education quality management, then generate appreciation and new ideas about the dilemmas or challenges that will be faced from the concepts of the analyzed articles. This research uses the article review method, which involves summarizing several published articles, comparing them, providing appreciation, and generating critiques and new ideas as a development of the scientific treasury. The result of this research is a review of several articles on the concept of multicultural quality education management as one approach to optimizing the function of education in accordance with the diverse ethnic, cultural, and religious conditions of Indonesian society. The study contributes positively to the field of management science, but the dilemma of it, also have some risks in creating a negative stigma about cultural diversity. If not implemented correctly, it would be better for multicultural education management to focus more on improving human resources with an approach rooted in Indonesian nationalism.